2021
DOI: 10.3390/agriculture11121204
|View full text |Cite
|
Sign up to set email alerts
|

Application of Essential Oils for Maintaining Postharvest Quality of ‘Rongrien’ Rambutan Fruit

Abstract: The postharvest quality of rambutan fruits (Nephelium lappaceum Linn.) is mainly influenced by dehydration, which causes browning of the peel and spinterns. This research investigated the effects of some essential oils—from citronella, clove, kaffir lime, and lemongrass—on ‘Rongrien’ rambutan fruit quality during storage at 13 °C. Screening of effective concentrations from 0.01 to 0.16% was conducted for each essential oil. The results showed that, of the essential oil treatments tested, a kaffir lime oil coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Based on our results, CH might be able to mitigate the negative effects that EOs can have on the dehydration of food products, improving the water barrier properties. Similarly to our observation, Ummarat and Seraypheap [ 52 ], studying the post-harvest effects of EOs on rambutan fruits ( Nephelium lappaceum Linn.–Sapindaceae), found that Cymbopogon nardus L. (Poaceae) EO at concentrations higher than 0.04% enhanced the weight loss compared to their CTR.…”
Section: Discussionsupporting
confidence: 87%
“…Based on our results, CH might be able to mitigate the negative effects that EOs can have on the dehydration of food products, improving the water barrier properties. Similarly to our observation, Ummarat and Seraypheap [ 52 ], studying the post-harvest effects of EOs on rambutan fruits ( Nephelium lappaceum Linn.–Sapindaceae), found that Cymbopogon nardus L. (Poaceae) EO at concentrations higher than 0.04% enhanced the weight loss compared to their CTR.…”
Section: Discussionsupporting
confidence: 87%
“…Namely, a high concentration of essential oils might have the side effect of causing color change disorders [34]. In addition, high essential oil concentrations have been reported to have caused damage to the fruit, including severe peel burn and browning, thus affecting the fruit's appearance [34,35]. This observed phenomenon may be attributed to high concentrations of essential oils, which cause structural alterations in the cellular components of phospholipids, fatty acids, and polysaccharides, leading to cellular toxicity and disrupting their normal functions [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Customers therefore demand products that are guaranteed as well as the complete preservation of sensory qualities, biological and nutritional contents. Food technologists and consumers can benefit greatly from a conservation strategy that tackles these issues [14,15]. Biopolymers are a promising resource for a sustainable planet in the future since they are abundant, renewable, and biocompatible materials.…”
Section: Introductionmentioning
confidence: 99%